Maths
posted by Anonymous .
Express the sum using summation notation:
1  1/2 + 1/3  1/4 + 1/5  ... (to 3n terms)
If I'm doing this right so far, with k=1 (the number on bottom of the sigma), the equation after the sigma would be
((1)^(k+1)) / k
I'd be able to figure out the term on top of the sigma, n, if I knew the value, but I don't understand how to get it because of the way it is worded. Please help, and correct me if what i've done so far is wrong.
Respond to this Question
Similar Questions

further mathematics
The roots of the eqn, x^4 + px^3 + qx^2 + rx + s = 0 where p, q, r, s are constants and s does not equal to 0, are a, b, c, d. (i) a^2 + b^2 + c^2 + d^2 = p^2 2q (in terms of p & q) (ii) 1/a + 1/b + 1/c + 1/d = r/s (in terms of r … 
math
Hi. I'm having trouble with the summation of n from i=2 of ((2^ni)(2^n)). Any help would be greatly appreciated! the way I am reading the question you have i is going from 2 to n so there will be n1 terms using i = 2,3,4,..,n I get … 
Maths
Express the sum using summation notation: 1  1/2 + 1/3  1/4 + 1/5  ... (to 3n terms) If I'm doing this right so far, with k=1 (the number on bottom of the sigma), the equation after the sigma would be ((1)^(k+1)) / k I'd be able … 
Maths
Express the sum using summation notation: 1  1/2 + 1/3  1/4 + 1/5  ... (to 3n terms) If I'm doing this right so far, with k=1 (the number on bottom of the sigma), the equation after the sigma would be ((1)^(k+1)) / k I'd be able … 
Algebra
Express the sum below using summation notation. Use 1 as the lower limits of summation and i for the index of summation. 1/3+2/4+3/5+...+18/20 
PreCalcPlease check
Please check: 1.Write in expanded form: this is a sigma notation 4 on top signma in middle k=1 on bottom to right of sigma is (k1)(k2) I solved: k=1 (11)(12)=0(1)=0 K=2 (21)(22) = 1(0)=0 k=3(31)(32)=2(1)=2 k=4 (41)(4)=3(2)=6 … 
Calculus need help badllyyy!
Use the expressions for left and right sums and the table below. righthand sum = summation (n above and i =1 on the bottom) f(ti) * change in t = f(t1) * change in t + f(t2) * change in t + .... + f (tn) * change in t lefthand sum … 
Math help quickly
Use the expressions for left and right sums and the table below. righthand sum = summation (n above and i =1 on the bottom) f(ti) * change in t = f(t1) * change in t + f(t2) * change in t + .... + f (tn) * change in t lefthand sum … 
MATH
Expand f(x)=ln (1+x/1x) in a Taylor Series about x=0. You must express your answer using summation notation. This is what I tried to do So I was thinking of taking the derivative of ln(1+x/1x) and get 2/x^21 And then use the … 
Algebra 2
Q: What represents the sum of a geometric series with 8 terms whose first term is 3 and common ratio is 4. A: 65,535 Is my answer right?